Jasser Auda's Review of Maqashid Syari'ah on PP No. 45 of 1990 Concerning Amendments To PP No. 10 Of 1983 Concerning Marriage And Divorce Permits For Civil Servants - Cut Nadya Nurizky (Tunas Institute, 2024)
Civil Servants (PNS) play an essential role in the administration of government and public services. Their performance is influenced not only by work professionalism but also by family life conditions. To maintain the stability and integrity of civil servant families, the government has issued regulations governing marriage and divorce, one of which is Article 5 Paragraph (2) of Government Regulation No. 45 of 1990. This regulation grants superiors the authority to provide consideration regarding a civil servant’s request for divorce. However, this provision differs from Islamic law, which views divorce as a private matter between husband and wife, without external intervention. This study aims to examine the provisions of Article 5 Paragraph (2) of Government Regulation No. 45 of 1990 from the perspective of maqashid shari’ah as proposed by Jasser Auda. The research uses a library research method with a normative descriptive and descriptive-analytical approach. The findings show that the regulation aligns with contemporary maqashid shari’ah, particularly in terms of hifz an-nasl (protection of the family) and hifz al-‘ird (preservation of dignity and human rights), as interpreted by Jasser Auda. The superior’s authority in granting divorce permission is considered a form of institutional protection for the stability of civil servant families, as well as an effort to resolve conflicts peacefully and with dignity.